Home-to-Campus Commuting Mode Choice Among University Students in a Small-Scale City: A Mixed Multinomial Logit Analysis of Sustainable Mode Preferences - Peker, Raziye; Yardim, Mustafa Sinan; Akalin, Kadir Berkhan (MDPI, 2026)
Rapid growth in urban population, vehicle ownership, and spatial expansion places increasing pressure on urban transportation networks, necessitating a shift toward sustainable mobility solutions. Accordingly, this study examines the determinants of university students' mode choice preferences for home-to-campus commuting in a small-scale city. The analysis incorporates socio-demographic factors, mobility resources, and travel attributes as potential influencers of mode choice. For modeling preferences, a Multinomial Logit (MNL) model was initially used to estimate deterministic effects, followed by a Mixed Multinomial Logit (MMNL) model to capture unobserved heterogeneity at the individual level. The results demonstrate that gender, vehicle ownership, and travel distance play statistically significant roles in mode choice. Crucially, the MMNL analysis reveals that while students' sensitivity to travel time is relatively homogeneous, their sensitivity to travel cost exhibits significant unobserved heterogeneity. Moreover, the study reveals the potential for a modal shift toward sustainable options such as walking, cycling, and public transport. These findings offer valuable insights for promoting sustainable urban mobility and developing data-driven transport policies, specifically in alignment with the Sustainable Cities and Communities goal of the United Nations (UN) Sustainable Development Goals (SDGs).
Keywords: active transport; sustainable mobility; mixed multinomial logit; mode choice; travel behavior; TRANSPORT; MOBILITY; ATTITUDES; Science & Technology - Other Topics; Environmental Sciences & Ecology